Producer Services Openness and the Development of Servitization: The Perspective of Two-Way Openness - Wei Chen; Yinzhong Chen; Yifei Hao; Sili Chen (Discrete Dynamics in Nature and Society)
This paper brings producer services “bringing in” and “going out” into the same analytical framework and explains the influence mechanism of producer services opening on the development of servitization from three aspects of import trade, FDI, and OFDI. On this basis, using the latest input-output data of WIOD, this paper constructs some indicators to measure the openness of producer services such as import trade penetration, FDI penetration, and OFDI penetration and then empirically tests the impact of producer services openness on the development of servitization in China. The results show that the openness of producer services has a significant positive impact on the development of China’s servitization. In addition, the robustness analysis based on variable substitution and different estimation methods shows that the conclusions are robust. The heterogeneity test shows that the impact of producer services openness on servitization has heterogeneity. The specific performance is as follows: there is different impact of producer service sector openness on the development of servitization; the impact of producer service openness on the development of servitization with different factor intensities is also different; and there is also different impact of producer service sector openness on the development of servitization with different factor intensities. The policy implications of these research conclusions are as follows: firstly, taking co-construction of the “Belt and Road” as a chance to promote the new open pattern; secondly, focusing on expanding the openness of high-end producer services; and thirdly, taking innovation driven development as the guide to increase R&D investment of producer services.